2022
DOI: 10.1108/ijopm-04-2022-0277
|View full text |Cite
|
Sign up to set email alerts
|

Examining the link between integrated management systems and firm performance: do the integration strategies matter?

Abstract: PurposeThis study attempts to examine the performance differences between firms with and without integrated management systems (IMSs), and the impact of three integration strategies (i.e. implementing quality management system (QMS) first, then environmental management system (EMS) (QMS + EMS); implementing EMS first, then QMS (EMS + QMS); implementing QMS and EMS simultaneously (QMS − EMS)) on firm performance to reveal the IMS–performance relationship and provide empirical evidence.Design/methodology/approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…The benefits of integrating management systems are well-documented in the literature (Barbosa et al. , 2022; Wang and Liu, 2023), which supports the standpoint that asset management must be understood, applied strategically and integrated (Alsyouf et al. , 2021; Onyeaso and Johnson, 2006).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The benefits of integrating management systems are well-documented in the literature (Barbosa et al. , 2022; Wang and Liu, 2023), which supports the standpoint that asset management must be understood, applied strategically and integrated (Alsyouf et al. , 2021; Onyeaso and Johnson, 2006).…”
Section: Discussionmentioning
confidence: 68%
“…Considering these variables, the joint implementation of the ISO 31000 standard for risk management (ISO, 2018b) and the ISO 55001 can be a fruitful approach for organizations to better manage the risks associated with asset management, as the standard presents requirements and guidelines for establishing an efficient risk management system. The benefits of integrating management systems are well-documented in the literature (Barbosa et al, 2022;Wang and Liu, 2023), which supports the standpoint that asset management must be understood, applied strategically and integrated (Alsyouf et al, 2021;Onyeaso and Johnson, 2006).…”
Section: Analysis Of Asset Management Difficultiesmentioning
confidence: 77%
“…Charef (2022) looked at the effect of EMS on Brazilian businesses' environmental sustainability in another study. According to Wang and Liu (2023), businesses using EMS outperformed those without EMS in terms of pollution avoidance, energy conservation, and waste reduction. Some research, meanwhile, has also produced contradictory findings.…”
Section: Ems-organization and Environmental Sustainabilitymentioning
confidence: 99%
“…In turn, this enhanced reputation and brand value may well translate into tangible benefits, such as increased sales and a larger share of the market. The evolving landscape of consumer preferences and business practices further underscores the significance of environmental policy for the brick industry in Pakistan (Wang & Liu, 2023). A growing number of consumers and businesses are actively seeking environmentally sustainable products and services.…”
Section: Introductionmentioning
confidence: 99%
“…This is so because it provides a competitive edge to the businesses via the combination of quality management, environmental management, and occupational health and safety (Marinello & Dinicolò, 2019) This integration enables companies to differentiate their products and services in the global market that confers them with a competitive advantage as well as increasing their export potential. For instance, Wang & Liu (2023) found that there was a positive correlation between adoption of IMS and market share of firms implying that adoption of IMS can enhance export performance. The results also indicated that an integrated system had implications for a company's financial performance which means it has impacts on sales or export performance too.…”
Section: The Effect Of Ims Adoption On the Export Performance Of Firmsmentioning
confidence: 99%